Effect of infill pattern on the microstructure and properties of copper processed through metal fused filament fabrication technique - Salethkumar Jasper; Manickam Ravichandran; Chander Prakash; N. Radhika (Journal of Materials Research and Technology, 2025)
The future of production could be greatly impacted by additive manufacturing (AM) because of its advantages, such as reduced material usage, flexible geometry, and automation in the industry. Metal fused filament fabrication (MFFF) is one of the promising AM method for creating metallic components in an accessible and affordable manner. This work reports the how infill patterns affect the densification, microstructural integrity, and functional performance of copper parts fabricated using MFFF. This experimental study uses copper (Cu) as the feedstock material and investigates how the infill pattern affects the mechanical properties of metal objects made with fused filament fabrication (FFF). The results demonstrate that Cu samples with triangular infill have a higher hardness of 55HV and a higher compressive strength when compared to solid and gyroid infill. The solid infill has a higher ultimate tensile strength of (188.61 MPa) than the triangular and gyroid infill. A scanning electron microscope (SEM) was used to study the test specimens' internal structure and average pore size. Wear study results indicate that the gyroid infill pattern has low wear rate.